Pengaruh Kompensasi Terhadap Kinerja Karyawan PT. BANK Sumut Syariah KCP Stabat - Sumira, Kamaliah R, Asmawarna Sinaga (CV. Pusdikra Mitra Jaya, 2023)
The research aims to determine the effect of compensation on the performance of employees of PT. Bank SUMUT Syariah KCP Stabat. The source of this research data was obtained from the answers to the questionnaire given by the research respondents, namely all employees at PT. Bank SUMUT Syariah KCP Stabat. Data analysis in this study used validity test, reliability test, normality test, hypothesis test, and simple linear regression analysis. Based on these tests it is explained that compensation has a significant effect on the performance of employees of PT. Bank SUMUT Syariah KCP Stabat. This was obtained through the results of hypothesis testing, namely the t test which showed a significant value less than 0.05 or (0,04 < 0,05) and tcount > ttable (3,521 > 2,16037) so that there was an effect of variable X on variable Y. The compensation given by PT. Bank SUMUT Syariah KCP Stabat affects employee performance by 44,9%, while the rest is influenced by other variables such as experience, work discipline, and others. There is a positive or parallel relationship between Compensation and Employee Performance, the better the compensation given by PT. Bank SUMUT Syariah KCP Stabat, employee performance will also increase, and vice versa if the compensation provided is not good, employee performance will also decrease.